Governança na saúde pública: a procedimentalização da autotutela administrativa enquanto instrumento de racionalização da Política Nacional de Assistência Farmacêutica sob o paradigma da participação democrática na administração pública - Alana Lúcio de Oliveira (2014)
The judicialization of health, a phenomenon that is inserted into the theme of the judicialization of public policy, demands the design of new surroundings to the public behavior and the management of public actions in the area of health, especially with regard to public pharmaceutical assistance policy, given the significant sacrifice that prints in the fundamental rights, the high cost to the exchequer related to high rates of legal suits, and the risks of civil and criminal liability. In an environment of Democratic State of Law and consolidation of governance, which rises as a tool for achieving of the democracy the society participation in public determinations, makes it crucial to implement mechanisms for the involvement of society in decision-making policy in favor of the effectiveness of the fundamental right to health erecting a new concept of citizenship. The development of a dialogic procedure to the society participation in public spaces, in which citizens can act as a subject of rights and the Directors may revise its behavior with ballast self-correcting duty in the public interest, is presented as a measure of coping with the reality of excessive litigation and brings democratic beacons and shaps the behavior of public officials. The main objective of this research is therefore to carry out a theoretical study of the administrative proceduralizing self-correcting in the area of public pharmaceutical policy for care facility, defining its contours, coping with the present controversial issues in doctrine and jurisprudence. The methodology of the work will also involve the completion of a review about the profile of the legalization of health in the State of Minas Gerais from informations collected by the State Department of Health and Public Advocacy Office of the State of Minas Gerais. Will be to promote, this way, through research, a critique that incorporates both the failures and distortions as the positive potential of the institute, for, in the end, suggest changes and adaptations, from the perspective of democratic rule of law and governance.